Instructional Materials and Alternative Teaching Practices in Physical Education - Emy A. Morbo (Universitas Pendidikan Indonesia (UPI), 2021)
In physical education (PE) learning, one of the main problems faced by PE teachers is the lack of facilities and equipment. Therefore, it is necessary to find a better solution to solve this problem. This study used a descriptive evaluative and comparative research design to determine the level of achievement of the context, input, process, and product evaluation components in the learning program. This research was conducted in 3 selected schools in the Maguindanao Division-1, Philippines. The results show that books are used